Roles of Sema3A and VEGF165 in cortical neurons and vascular endothelial cells during oxygen glucose deprivation stimulation - Yang, Ying; Li, Chen; Wang, Ruili; Wang, Hui; Ma, Qiaoya; He, Ya; Zhang, Pengbo (Cellular and Molecular Biology, 2019)
To investigate the expressions and roles of semaphorin3A (Sema3A) and vascular endothelial growth factor 165 (VEGF165) in cultured rat cortical neurons and vascular endothelial cells after oxygen glucose deprivation (OGD) stimulation. Cultured cortical neurons (NC) and vascular endothelial cells (VEC) of Sprague Dawley (SD) rats (SPF grade) were randomly divided into control group and OGD treatment group. Western blot assay, immunofluorescent staining and immunohistochemical methods were used to determine the expressions of VEGF165, Sema3A and neuropilin-1 (Nrp-1) protein. Cell migration was determined by Transwell, while TUNEL assay was used to measure apoptosis. The expressions of Sema3A, Nrp-1 and VEGF165 in NC and VEC cells after OGD treatment were up-regulated, when compared with the control group. With transfection of Sema3A shRNA, apoptosis of neurons decreased significantly after 2 h of OGD treatment, but the apoptosis of VEC cells was not obvious. The migration rate of VEC cells in the treatment group was significantly increased, relative to that of the control group. Stimulation with OGD induces neuronal expression of VEGF165 and regulates the migration of vascular endothelial cells, thereby enhancing their participation in angiogenesis, which may involve Sema3A.